In Search of the Neanderthals: Solving the Puzzle of Human Origins - Stringer, Christopher and Gamble, Clive (London Thames and Hudson, cop., 1993)
Ever since the first discovery of their bones, the Neanderthals have provoked controversy. Who were they? How were they related to modern people? What caused their disappearance 35,000 years ago? The Neanderthals have become the archetype of all that is primitive. But what is their true story? Today Neanderthal specialists are locked in one of the fiercest debates in modern science. One side, the "multiregional" school, argues that the Neanderthals and their contemporaries evolved semi-independently into modern humans. Christopher Stringer leads the "out of Africa" school, which believes that the Neanderthals were replaced by modern people from Africa. Here he sets out his views for the first time, with the archaeologist Clive Gamble. Step by step the authors put forward their case. The Neanderthals had an anatomy crucially different from our own, adapted to Ice Age Europe. Neanderthal behaviour similarly points to fundamental differences. New genetic evidence strongly suggests a single origin for modern humans in Africa. The authors argue that, capable and intelligent as the Neanderthals were, they proved no match for the better-organized, better-equipped newcomers, and died out.
Includes Colored Illustrations, Bibliography and Index.
Keywords: Neanderthals